Effects of Blank-Qwerty-Touch Method and Performance of Business Education Students in Keyboarding in Federal College of Education, Kano, Nigeria - Auwalu, Ado; Amoor, S.S. (European Scientific Journal, ESJ, 2019)
The study was carried out to determine the effects of blank-qwertytouch method on performance of business education students in keyboarding in Federal College of Education, Kano, Nigeria. The study had two objectives, two research questions, and two null hypotheses which were formulated and tested at 0.05 level of significance. A Quasi-experimental design was adopted for the study. The population of the study was 60 business education students who were admitted in 2015/2016 academic session in Federal College of Education, Kano, Nigeria. The sixty (60) students were used for the study as intact class. The instruments used to generate data for the study were two selfdesigned Keyboarding Skills Tests (Pre-test and Post-test). Mean and standard deviations were used to answer the stated research questions. Simple Regression Analysis (SRA) was used to test null hypotheses one, while t-test statistics was employed in testing null hypotheses two. From the results of the study, hypotheses one was rejected while hypothesis two was retained. The study showed that students in blank-QWERTY-touch teaching methods performed better than those in the conventional (QWERTY-touch) method, and gender did not show any significant difference in the performance of students taught keyboarding using blank-QWERTY-touch methods. It was concluded therefore that, blank-QWERTY-touch teaching method has effect on students’ performance particularly at beginning of keyboarding training. Based on the findings, it was recommendation among others that, in order to make students develop high speed and accuracy, and ensure key position memorization at very beginning, keyboarding teachers should use the blank- QWERTY-touch method.